The use of etymology in learning Human Anatomy: a technical and methodological experience (Research, Society and Development, 2023)
Anatomy is the science that studies the structure and organization of living things, including their organs, tissues, systems and other structures. Many words used in anatomy have Greek or Latin origins, as these languages have been widely used by doctors and scientists throughout history. The study of the etymology of words can be a valuable tool for teaching Human Anatomy, as many terms have specific meanings and understanding the root and interpretation of these words, can bring students a better understanding of the anatomical system and its functions. The present experience report used this methodology as a way to improve academic learning, in a class of the 1st period of the Pharmacy course at the Federal University of Piauí. The students were divided into six groups where each of them made a banner, guided by the teacher and the team of monitors. Each banner contained two anatomical terms with: images, etymological origins, functions and the relationship of etymology with some characteristic of these anatomical structures, whether physical or historical, in addition to bibliographical references. After making the banners, the groups presented them to the whole class. In addition, they also produced educational videos that were made available to the entire social body through the main digital platforms. With this type of methodology, we aim to arouse interest in the formation of words not only in students, but in a larger audience, so that it helps in dynamic learning and interest in the subject, which is often challenging.